Efficacy of Ethanol Extract of Sambiloto (Andrographis paniculata) Against Pneumonia-Causing Klebsiella pneumoniae - Sulistiyawati, Indah; Falah, Muhammad; Nurasih, Ari Dwi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2025)
Klebsiella pneumoniae is one of the most common pathogens in nosocomial respiratory infections. Antibiotics are often used for the treatment of K. pneumoniae infections. Increased bacterial resistance to antibiotics is closely related to the success rate of infectious disease therapy. The use of plants as phytopharmacology is currently an alternative treatment. Some medicinal plants that have antibacterial and immunomodulatory activity are Sambiloto (Andrographis paniculata) with an active compound called andrographol. The purpose of this study was to provide a solution to the problem above by developing a phytopharmaceutical using bitter extract to inhibit the growth of K. pneumoniae bacteria. Two sputum samples from the laboratory confirmed Covid-19 patients with pneumonia infection at the Hospital. The sambiloto was extracted by using 96% ethanol. The extract was further analyzed for its antimicrobial activity and phytochemical compounds. There were two K. pneumoniae isolates, namely KpRNG and KpTRI. The active compounds were saponin and steroids. The antimicrobial activity of the ginger extract was measured with different concentrations of 25%, 50%, 75%, and 100%. Its inhibitory zone against K. pneumoniae was ranging from 5.8 to 7 mm or had a moderate inhibition category.